Augmented Reality Platform for Collaborative E-Maintenance Systems - Benbelkacem, Samir; Zenati-Henda, Nadia; Zerarga, Fayçal; Bellarbi, Abdelkader; Belhocine, Mahmoud; Malek, Salim; Tadjine, Mohamed (IntechOpen, 2011)
None